Nursing knowledge as relational ontology: Toward an enacted, technologically mediated, and globally situated understanding of nursing - Gil P. Soriano; Feni Betriana; Kathyrine Calong Calong; Joseph Andrew Pepito; Tetsuya Tanioka; Rozzano Locsin (Belitung Nursing Journal, 2026)
Despite substantial theoretical advancement, nursing knowledge continues to be framed by epistemological classifications rather than ontological clarification. The question of what nursing knowledge is, as a mode of existence, remains unanswered, despite existing frameworks that emphasize patterns, types, or domains of knowing. This paper argues that nursing knowledge is best understood as a relational ontology, a performative enactment emerging through practice rather than a collection of categorized components. Nursing knowledge is conceptualized as a unitary process manifested through embodied presence, interpretive meaning-making, and technologically mediated action. This paper illuminates how these aspects do not function as distinct domains but as a single, inseparable mode of being in clinical judgment and caring practices within digitally mediated contexts.